2017
DOI: 10.1212/wnl.0000000000004088
|View full text |Cite
|
Sign up to set email alerts
|

CSF sAPPβ, YKL-40, and neurofilament light in frontotemporal lobar degeneration

Abstract: This study provides Class III evidence that CSF levels of sAPPβ, YKL-40, and NfL are useful to identify patients with FTLD-related syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 36 publications
13
89
2
Order By: Relevance
“…Our previous study reported that the combination of CSF sAPPβ with YKL-40 in clinically defined patients had a good diagnostic performance in a clinical setting to distinguish frontotemporal dementia from AD and cognitively normal controls 16. The present study extends these findings to patients with neuropathological confirmation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our previous study reported that the combination of CSF sAPPβ with YKL-40 in clinically defined patients had a good diagnostic performance in a clinical setting to distinguish frontotemporal dementia from AD and cognitively normal controls 16. The present study extends these findings to patients with neuropathological confirmation.…”
Section: Discussionsupporting
confidence: 73%
“…In our previous study of these CSF analytes in clinically diagnosed patients,16 we did not detect differences between patients with high likelihood of FTLD-Tau and patients with high likelihood of FTLD-TDP. The present study examines these analytes in patients with neuropathological confirmation.…”
Section: Discussioncontrasting
confidence: 68%
“…CSF samples from the SPIN cohort have contributed to several international multicenter CSF biomarker studies [34][35][36][37][38]. The SPIN cohort has contributed to the characterization of different CSF biomarkers such as b-site APP-cleaving enzyme activity [39,40], sAPP-b [6,39,41], neurofilament light chain [41], YKL-40 [6,39,[41][42][43], progranulin [44], a panel of synaptic proteins [45], and mitochondrial DNA [46] in different neurodegenerative diseases. In addition, the collection of paired blood and CSF samples offers the possibility to investigate the correlation of biomarker levels between these two compartments [15,44].…”
Section: Resultsmentioning
confidence: 99%
“…However, CSF NfL is a nonspecific disease biomarker that is upregulated in other disorders such as AD 27, 32, 34. Importantly, recent studies showed that the ratio between NfL and the soluble β fragment of amyloid precursor protein (sAPP β )53 or the combination of TDP43 with p/tTau ratio54 could optimally discriminate FTLD patients from CON in a large cohort, promising data that need to be replicated in independent cohorts. An additional challenge in clinical practice is the differential diagnosis of dementia.…”
Section: Discussionmentioning
confidence: 99%